2014
DOI: 10.1177/016264341402900301
|View full text |Cite
|
Sign up to set email alerts
|

iPad® or iPod Touch®: Evaluating Self-Created Electronic Photographic Activity Schedules and Student Preferences

Abstract: Five secondary students with intellectual disability (ID) participated in a withdrawal design (A-B-A-B) study evaluating the effectiveness of a self-created electronic photographic activity schedule (ePAS). After learning to take photos of various activities using an iPod touch® or iPad®, students learned to use the First Then Visual Schedule application to self-manage task directives. The dependent variables included the percentage of tasks independently and correctly completed and the percentage of steps cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 14 publications
(8 reference statements)
4
26
0
Order By: Relevance
“…The results from this study showed that individuals could independently program the electronic device and select their own exercises, which supports previous researchers who believed that individuals will become more independent if taught to create their own schedule (Douglas & Uphold, 2014;Duttlinger et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results from this study showed that individuals could independently program the electronic device and select their own exercises, which supports previous researchers who believed that individuals will become more independent if taught to create their own schedule (Douglas & Uphold, 2014;Duttlinger et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Electronic PAS (ePAS), which provide picture prompts on an electronic device (e.g., iPod touch®, smartphone, tablet computer), have also been shown effective (Cihak, 2011;Cihak, Kessler, & Alberto, 2008;Douglas & Uphold, 2014). As society embraces self-management technology, our efforts to assist students with self-managing tasks should include these technology tools.…”
Section: Research-article2014mentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of this study expanded the literature base in a few ways. First, allowing students to independently use their electronic device is important for promoting daily living skills (Douglas & Uphold, 2014; Kelley, Rivera, & Kellems, 2016; Uphold, Douglas, & Loseke, 2016). For instance, the students in this study learned how to use an iPod touch or an iPad to create grocery lists.…”
Section: Discussionmentioning
confidence: 99%